Industrializing English law : entrepreneurship and business organization, 1720-1844 - Harris, Ron, 1960- (Political economy of institutions and decisions., 2000)
Annotation Between 1720 and the mid-nineteenth century, the legal framework of England remained static, while the country went through an economic and social evolution known as the Industrial Revolution. This book addresses the apparent discrepancy between the developing economy of 1720-1844 and the stagnant legal framework of business organization during the same period. The book specifically focuses on the ways by which the legal-economic nexus of the period gave rise to the modern institutions of organizing business.